9m+10-4m=-5

Simple and best practice solution for 9m+10-4m=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9m+10-4m=-5 equation:


Simplifying
9m + 10 + -4m = -5

Reorder the terms:
10 + 9m + -4m = -5

Combine like terms: 9m + -4m = 5m
10 + 5m = -5

Solving
10 + 5m = -5

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 5m = -5 + -10

Combine like terms: 10 + -10 = 0
0 + 5m = -5 + -10
5m = -5 + -10

Combine like terms: -5 + -10 = -15
5m = -15

Divide each side by '5'.
m = -3

Simplifying
m = -3

See similar equations:

| (5/9)x^2-(16/5)x-3/2=0 | | 10s-6s-3s-1=13 | | 3(8-x)-5=-6x-4+3n | | 3x-10+2x=-65 | | t(n)=-6+3(447-1) | | 4(6-9)/6= | | 8-(-4)2-5= | | 5b-b-1=7 | | 2qt=c | | 8x+3y=37 | | 3(t)=67-16t^2 | | p(x)=5x^2-3x+2 | | t(n)=24-5(447) | | 19w-9w-9w+3=20 | | 8x=37-3y | | -3x+3=2x | | (3x+1)(1x+2)= | | 8n=15model | | Xy=126 | | 14n-13n=15 | | 8n=15midel | | 5h+4=34 | | 12/(1/9) | | -2/3(5/6x-3)= | | t(n)=5(447)-3 | | 7/8x=14/40 | | -2/5-7/10= | | 16k+k-14k-2=16 | | 4(1/9) | | -2x^2+2x+17=0 | | 0.02x+0.07(7000-x)=320 | | 3x^2/3-11x^1/2-4=0 |

Equations solver categories